ANALISIS IPMA PENERIMAAN PENGGUNAAN TEKNOLOGI LEARNING MANAGEMENT SYSTEM (LMS): Mahasiswa Universitas Telkom - Khairani Ratnasari Siregar; Indira Rachmawati; Heppy Millanyani; Monica Esperanza (Jurnal Sosioteknologi, 2022)
The current COVID-19 pandemic is causing big problems around the world, including in the world of education, which is experiencing changes in its learning system. Distance learning is now used by all universities in Indonesia due to the impact of the pandemic. Telkom University makes e-learning technology called CeLOE Learning Management System (LMS) as a distance learning platform for all lecturers and students. The purpose of this study is to determine the importance rating by using IPMA of the factors that influence the acceptance of CeLOE LMS technology using the General Extended Technology Acceptance Model for E-Learning (GETAMEL). The minimum sample in this study amounted to a minimum of 379 samples of respondents conducted by CeLOE LMS users. This study uses a non-probability sampling technique and the analysis technique used in this study is PLS-SEM using Smart PLS 3.2.9 software.